Kewujudan Allah SWT Menurut Tuan Minal: Analisis dan Transliterasi Teks Aqīdat al-Najīn - Abd Latif, Faizuri; Wan Abdullah, Wan Suhaimi (Afkar: Jurnal Akidah dan Pemikiran Islam, 2009)
This article attempts to ‘revive’ the legacy of one of the great Muslim scholar in Southeast Asia Sheikh Zainal `Abidin al-Fatani, who is also known as Tuan Minal. It analyses Tuan Minal commentary on ‘Umm al-Barahīn by al-Sanusī particulary on the existence of God. It presents a brief introduction on Tuan Minal and his work `Aqīdah al-Najīn together with an analysis of Tuan Minal commentary on the existence of God. It also proposes a romanized version of the selected texts related to the existence of God from `Aqīdah al-Najīn. The article concludes that Tuan Minal had played a great role in assuring the continuity of the Ash`arite theology in the Malay world and that his commentary on the Sunni theology is still relevance, with certain elaboration, for the moden Malay reader.